Victimization Reflected In John Grisham'sThe Confession Novel (2010):A Sociological Approach - Dewi, Kartika Candra, Dr. M. Thoyibi , M.S, Siti Fatimah , A M. Hum (2016)
This research is about a victim of crime who should die because of wrong execution in John Grisham's The Confession novel (2010) the researcher analyzed this novel using Sociological Approach which is wrote by Alan Swingewood and Diana Laurenson. The objectives of this study are to identify the characteristics of victimization, to classify the type of victimization based on John Grisham novel, describe the causes and impact of victimization, and the reasons why the author opened victimization in his novel. This research is a qualitative research. The primary data of this research is The Confession novel (2010) by John Grisham. The Secondary data are website, biography of the author, article and some books which related to the study. The conclusions of this research are; the main factors that lead victimization is an interrelated of individual factors of victims and perpetrators and psychological factors that influence the occurrence of victimization. Primary Victimization is a crime to individuals or which refer to individual victims who can be directly harmed victims physically and psychologically attack. And last, there are four impacts of victimization; Emotional Impact of Victimization, Physical Impact of Victimization, Financial Impact of Victimization, and Psychological Impact of Victimization.